ROLE OF OPHIOLITES IN ARCHIPELAGO MODEL OF OROGENESIS - Hsü K.J. (My University, 2003)
Ophiolites are mafic and ultramafic rock assemblages occurring in mountain belts, and they are commonly found in mélanges. Their association with deep-sea sediments suggests that they represent fragments of raised ocean floor. This conclusion is supported by marine geological and geophysical investigations. This paper presents the evolution of my own thinking on the origin of ophiolites. I interpret ophiolites as relics of the ocean floor of backarc basins on the basis of my own investigations in the Alps and in China, as well as of literature surveys. I have concluded that only rarely do ophiolites mark the suture zones of plate-collisions.
Keywords: ophiolite; mélange; backarc basin; archipelago; orogenesis